Evaluating the Use of Internet of Things Technologies in Chronic Diseases From the Perspective of Healthcare Providers - H. Saleh, Hana; wanes, Anfal; Salem, Astberq; Alghmari , Hussein; Abdullah, Thekra (Libyan Journal of Public Health Practices, 2026)
The healthcare sector has experienced notable advancement through the adoption of Internet of Things (IoT) technologies, particularly in chronic disease management. This study aimed to evaluate healthcare providers’ perceptions of the benefits and challenges associated with IoT implementation. A cross-sectional study was conducted among 150 healthcare providers using a structured questionnaire to assess perceived benefits and barriers to IoT adoption. The findings indicated a consensus regarding the significant potential of IoT technologies, with 70 participants acknowledging the role of these technologies in improving patient monitoring. However, major barriers to implementation were identified, including a lack of skilled personnel and weak technical capacity (79.3%), inadequate policies (76.7%), and high costs (60.6%). Despite positive awareness of IoT benefits, effective integration into healthcare systems requires addressing human and structural challenges by ensuring adequate infrastructure, qualified personnel, and clear regulatory frameworks.